2009
DOI: 10.1097/aog.0b013e3181a11c64
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Conservation at the Time of Hysterectomy and Long-Term Health Outcomes in the Nurses’ Health Study

Abstract: Objective To report long-term health outcomes and mortality after oophorectomy or ovarian conservation. Methods We conducted a prospective, observational study of 29,380 women participants of the Nurses’ Health Study who had a hysterectomy for benign disease; 16,345 (55.6%) had hysterectomy with bilateral oophorectomy and 13,035 (44.4%) had hysterectomy with ovarian conservation. We evaluated incident events or death due to coronary heart disease (CHD), stroke, breast cancer, ovarian cancer, lung cancer, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
466
4
15

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(502 citation statements)
references
References 26 publications
17
466
4
15
Order By: Relevance
“…Further, our finding that controlling for ovary exposure in parous females weakens the association between longevity and parity lends additional support to the idea that, independent of reproduction, ovaries are part of a system that promotes longevity. Taken together, our findings from this canine cohort echo results from women in which longer ovary retention is associated with a lowering of overall mortality (Parker et al 2009;Rocca et al 2006). Moreover, our conclusions are consistent with the hypothalamic-pituitary-gonadal (HPG) axis hypothesis of longevity proposed by Atwood and colleagues, in which longer lifetime gonad activity (i.e., delayed onset of menopause), rather than number of offspring, predicts longevity in women (Yonker et al 2011).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Further, our finding that controlling for ovary exposure in parous females weakens the association between longevity and parity lends additional support to the idea that, independent of reproduction, ovaries are part of a system that promotes longevity. Taken together, our findings from this canine cohort echo results from women in which longer ovary retention is associated with a lowering of overall mortality (Parker et al 2009;Rocca et al 2006). Moreover, our conclusions are consistent with the hypothalamic-pituitary-gonadal (HPG) axis hypothesis of longevity proposed by Atwood and colleagues, in which longer lifetime gonad activity (i.e., delayed onset of menopause), rather than number of offspring, predicts longevity in women (Yonker et al 2011).…”
Section: Discussionsupporting
confidence: 79%
“…By establishing a cohort of canine "centenarians" -exceptionally long-lived Rottweiler dogs who lived more than 30 % longer than the average life expectancy for the breed -we discovered that longer duration of lifetime ovary exposure was associated with increased likelihood of exceptional longevity (Waters et al 2009). This finding remarkably parallels recent data on the possible lifespan-and healthspanpromoting effects of ovaries in women (Parker et al 2009;Rivera et al 2009;Rocca et al 2006Rocca et al , 2009. Here, we compare the complete reproductive histories of this valuable cohort of exceptionally long-lived female Rottweilers to a cohort of female Rottweilers with usual longevity.…”
Section: Introductionsupporting
confidence: 69%
“…The survival rate of 10%-30% has been observed in women with advanced ovarian carcinoma (stage III-IV) using surgical cytoreduction (total abdominal hysterectomy, bilateral salpingo-oophorectomy, pelvic and para-aortic lymph node removal, and omentectomy), followed by platinum-based chemotherapy [84] . In another study, it was concluded that bilateral oophorectomy at the time of hysterectomy resulted in increased risk of all-cause mortality, fatal and nonfatal coronary heart disease, and lung carcinoma [85] . A study conducted on platinum-sensitive patients diagnosed with ovarian carcinoma to compare the efficacy of single (platinum alone) versus combinational chemotherapies (platinum plus paclitaxel) concluded that patients administered with the combinational therapy had a significantly higher survival rate compared to those who received single chemotherapy [86] .…”
Section: Treatmentmentioning
confidence: 99%
“…Известно, что в периоде постменопаузы яичники до возраста примерно 80 лет продолжают вырабатывать такие андрогены, как те-стостерон и андростендион, которые участвуют в синтезе эстрогенов. По данным больших проспективных исследо-ваний со сроком наблюдения до 24 лет, аднексэктомия и последующая хирургическая менопауза приводят к увели-чению риска развития сердечно-сосудистых заболеваний, числа переломов шейки бедренной кости, психосексуаль-ных и умственных дисфункций [34][35][36][37]. В то время как заболеваемость раком яичников в возрастной группе 50 лет составляет примерно 1 на 1500, а в группе 60-70 лет -1 на 400-600 [38], эта патология остается относительно редкой, и ежегодно от рака яичников в США умирают 14 800 женщин, в то время как тот же показатель от сер-дечно-сосудистых заболеваний составляет 350 тыс.…”
unclassified